Committing An Affair In The Marriage Life: Readers’ Interpretation Of Virginia Woolf’s "the Legacy” - Trisnawati, Ririn Kurnia (Journal of English and Education (JEE), 2007)
Producing the interpretation of a literary work can be done by giving responses toward the work and employing the subjective criticism, one strain of the reader-response theory, can analyze that interpretation. This paper was aimed at describing and analyzing individual responses and die communal interpretations produced by the readers of Virginia Woolf s "The Legacy", particularly toward its theme about the affair case happened in the marriage life. It was also to find out the involvement of die subjective motive die readers possessed toward the production of their individual responses and the communal interpretations. The findings show that the readers produced individual responses along with the symbolization of their subjective motive, in terms of the personal experience of affair case in the marriage life, the personal belief about that affair and love, and the reading experience. In those individual responses, it was found both the identical and the various individual responses formed by the readers. The production of this identical  response involved the identical symbolization of the readers' subjective motive. The readers also had gone through the communal discussion and they approved two communal interpretations. Firstly, Angela's affair was common due to her unhappy marriage life condition. The reason was because the readers had experiences affair case similar to Angela's affair and her unhappy marriage life. This similar condition between Angela's affair and readers' personal experience influenced the readers to accept that as the communal interpretation. Secondly, the direct and indirect personal experience of affair case could cause a different position in responding to Angela's affair. It was because the distance the readers had. Another point was revealed that the readers had involved their subjective motive as the symbolization consciously.